Health-Related Utility of EQ-5D in Korean Adults With Chronic Urticaria: Mapping From Urticaria Outcome Measures - Lee, Min-Sang (Allergy Asthma Immunol Res, 2020)
PURPOSE: A need for useful measures reflective of the socio-economic burden of chronic urticaria (CU) has arisen. To obtain utility estimates for CU, we investigated EuroQol-5-Dimension (EQ-5D) indices according to urticaria control status and urticaria severity. METHODS: In this prospective observational study, we administered patient-oriented questionnaires on EQ-5D and urticaria outcomes, including Urticaria Activity Score over 7 days (UAS7), Urticaria Control Test (UCT), and CU-specific quality of life (CU-QOL). EQ-5D utility index scores were compared according to urticaria control status and disease severity. Conditional process analysis (CPA) was used to map EQ-5D utility scores from UAS7 and UCT. RESULTS: Greater EQ-5D utility values were obtained in patients with better urticaria control (0.91 ± 0.10 for well controlled CU, 0.84 ± 0.12 for partly controlled, 0.77 ± 0.14 for uncontrolled, P < 0.001). According to CU severity, mean utility values were ranged from 0.746 (severe, UAS7 ≥ 28) to 0.860 (moderate), 0.878 (mild), and 0.953 (urticaria free). CPA suggested that UAS7 was directly correlated with UCT (regression coefficient, −0.251; 95% confidence interval [CI], −0.278, −0.223; P < 0.001) and EQ-5D utility (−0.002; 95% CI, −0.003, −0.001; P = 0.007) after controlling for age, sex, urticaria duration, and combined allergic diseases. CONCLUSIONS: EQ-5D values increased with improvement in urticaria control and decreased with urticaria severity. A predictive model mapping EQ-5D utility from UAS7 and UCT scores suggested that EQ-5D can be useful for the pharmacoeconomic evaluation of individualized treatments for CU patients.